ANALISIS PENGAWASAN MENELAN OBAT PASIEN TUBERKULOSIS (TB) DALAM PROGRAM PENANGGULANGAN TB DI PUSKESMAS SEMPOR II KABUPATEN KEBUMEN - Nida Adyaningrum; Chriswardani Suryawati; Rani Tiyas Budiyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Sempor II Primary Health Care is one of the health centers with a success rate that has not yet reached the target set by the Kebumen District Health Office, which is 85%. Failure in the success of treatment causes a more severe TB disease condition which results in increased cases of MDR (Multi Drug Resistant), complications, and causes of death. One of the strategies in achieving the target of TB success rate and preventing drop out is by monitoring the ingestion of drugs. This study aims to analyze the supervision of swallowing drug of TB patients in the tuberculosis (TB) control program at the Sempor II Primary Health Care in Kebumen Regency in the input, process and output variables. This research was a qualitative research with descriptive analytic. Data was colected by in-depth interviews. The object of study was the Supervision of Drug Swallowing in the TB Control Program at the Sempor II Primary Health Care in Kebumen Regency, viewed from the input, process and output aspects. The results of research on the implementation of drug swallowing control activities carried out at the Sempor II Primary Health Care from input variables, there are obstacles in the aspects of human resources, funds and methods. While in the material aspects there are no obstacles In the process variables there are obstacles in the planning process and implementation and there are no obstacles in the mobilization process. Evaluation of drug swallowing control activities has never been done. The output variable found that regarding timeliness at the time of the supervision of the main informant one said that the supervision activities to swallow drugs, for home visits could not be on schedule. 90% of TB patients at the Sempor II Primary Health Care have carried out regular treatment even though they have not yet reached the target of success of the treatment that is set at 85%.